Pengaruh Kejelasan Sasaran Anggaran, Partisipasi Masyarakat, Pemanfaatan Teknologi Informasi dan Kompetensi Sumber Daya Manusia Terhadap Akuntabilitas Pengelolaan Dana Desa di Desa Se-Kecamatan Penebel - Ni Kadek Dwi Tasari; Ni Komang Sumadi; I Wayan Budi Satriya (UNHI Press, 2023)
Accountability is very important in managing village funds to provide assurance of public trust in the government and to bridge the gap between the government and the community. the author's writing is intended to know the impact of clarity on budget targets, the role of citizens, utilization of information technology and human resource competence on the accountability of managing village funds in villages throughout Penebel District. This study utilized a purposive sampling method with a sample size of 144 respondents. Data was collected through the administration of a questionnaire. The data analysis technique employed in this study involves the use of multiple linear regression analysis, the coefficient of determination, testing F, also t. The findings indicate that budget target clarity, community participation, information technology utilization, and human resource competence positively and significantly impact the accountability of village fund management.